Synthesis of Nanocellulose from Rubberwood Fibers Via Ultrasonication Combined with Enzymatic and Chemical Pretreatments - Poddar, Pradeep Kumar; Gupta, Arun; Saidatul Shima, Jamari; Ng, Siew Kim; Khan, Tanveer Ahmed; Sharma, Swati; Mohd Aizudin, Abd Aziz (Asian Online Journals, 2015)
This paper presents synthesis of nanocellulose from rubber wood (Hevea brasiliensis) fibers via ultrasonication combined with enzymatic and chemical pretreatments. Cellulose nanofibers were separated from rubber wood fibers in three distinct stages. Initially, rubber wood fibers were subjected to a series of enzymatic and chemical pre-treatments to eliminate lignin and hemicellulose. The obtained chemical-purified cellulose fibers were then mechanically separated into nanofibers using ultrasonication. The diameter distributions of the resulting nanofibers were dependent on the output power of ultrasonic treatment. The extent of dispersion improved significantly with increasing output power of ultrasonic treatment. Microscopy study showed that the diameters of the nanofibers isolated ranged from 8.7 to 20 μm. The effectiveness of laccase and xylanase enzymes was also studied. The results obtained from FTIR and thermo gravimetric analyses indicated that there were consistencies between the studied enzymes to the thermal stability or chemical structure. FTIR spectroscopy confirmed that the prominent peaks indicating that most of the lignin and hemicellulose were removed during the step-wise chemical treatment were present in the spectrum. FTIR spectroscopy suggested that the spectrum of cellulose nanofibers obtained under different ultrasonic output powers and chemical-purified cellulose fibers were similar, signifying that the molecular structure of cellulose were unaffected by the ultrasonic treatment. TGA results revealed that the thermal properties of cellulose nanofibers were enhanced and the thermal degradation temperature increased to proximately 310 °C as compared to 240 °C of the untreated rubber wood fibers. Results from this work may be potentially applied in various fields such as bio-nanocomposites, filtration media packaging, tissue engineering scaffolds, and so on.